SEMANTIC NOTION OF DIMINUTIVES IN THE FORMATION OF UZBEK AND ENGLISH. - Turdimatova, Madina (Журнал иностранных языков и лингвистики, 2021)
Diminutive research is often too narrowly focused on suffixed nouns, while other types of diminutive formation are neglected. A plea is therefore made to also consider other formation types including reduplication, compounding and periphrastic constructions. Furthermore, it is shown that a more differentiated account of diminutive meaning is needed than is currently available. It is suggested that an adequate semantic description, which can accommodate the various ambiguities of diminutives, can best be found in systematic corpus-based analysis of diminutives in context. Pragmatic approach is outlined which avoids the problems pertaining to diminutive formation and meaning and is particularly relevant for cross-lingual and typological studies. This approach is focused on the social functions of diminutives in specific types of contexts.